Development of low temperature gas sensing for detection of volatile organic compounds and methane derived from CeO2-TiO2 hetrostructure - Mabunda, Lanneth (My University, 2023)
Methane (CH4) is a foremost hazardous gas in coal mines because of its explosive behavior. At concentrations of 30 000 to 50 000 ppm, CH4 can result in an explosion. Though the current commercial obtainable noble metal/Al2O3 beads-based CH4 sensors show higher selectivity and sensitivity toward CH4 nonetheless, their operational temperature is extreme, i.e., 500−700 °C. Thus, at that temperature, the CH4 combustion on the catalysts generally leads to a high risk of explosion and complexity in fabricating the sensor. Therefore, is very vital to develop CH4 sensors that can function at lower temperatures. It is in the current study, the CeO2, TiO2, and TiO2-CeO2 heterostructures were prepared using the sol-gel method. The XRD analyses disclosed the formation of pure CeO2, TiO2, and TiO2-CeO2 heterostructure. While the surface analyses showed that nanostructures are made of nanoparticles. Moreover, the optical studies showed that the band of the pure CeO2, TiO2, and TiO2- CeO2 heterostructures is dependent on the synthesis temperature. The bandgap reduced when increasing the synthesis temperature for all the nanostructures. However, in terms of gas sensing, more especially for the detection of CH4, the CeO2, TiO2, and TiO2-CeO2 heterostructure-based sensors showed no sensing response at low operational temperatures, instead, the sensors could only function beyond 300 C, which was higher than the limit of our sensing station. In chapter 5, the n-n type of TiO2/CeO2, CeO2/TiO2, p-n-n type of Cr2O3/TiO2/CeO2 and p-n-n type of Cr2O3/CeO2TiO2-ternary heterostructures were pared using hydrothermal method. Structural analyses validated the formation of prepared heterostructures. While scanning electron microscopy showed that the nanostructures are made of nanoparticles. For gas sensing application, the sensors were tested toward various gases, including benzene, ethylbenzene, toluene (BTE), ethanol, carbon monoxide, methane (CH4), carbon dioxide (CO2), and nitrogen dioxide (NO2). Among the tested sensors, the Cr2O3/TiO2/CeO2-based sensor displayed a remarkable response and selectivity toward CH4 at a low operational temperature of 100 C. The higher response observed for the Cr2O3/TiO2/CeO2-based sensor towards CH4 was further validated by photoluminescence (PL) studies, which showed that the material consisted of higher oxygen vacancies (VO) which could be the reason for improved sensing performance. Additionally, the UV-vis analyses also confirmed that the material has a smaller bandgap, which denoted that the electrons were more inclined to change and resulting in more photogenerated carriers that could lead to enhanced sensing response and therefore lead to reduced sensing temperature. Therefore, these results denote that the Cr2O3/TiO2/CeO2-based sensor could be considered as the potential candidate for the detection of CH4 at low temperatures.
Thesis (M.Sc. (Physics)) -- University of Limpopo, 2023
Keywords: Methane; Lower temperatures; Sensor; Heterostructures; Detection; Gas leakage; Methane; Coalbed methane; Gas; Explosives -- Detection